ANALISIS SQUARE CUP DEEP DRAWING - Uud Achmad Imadudin; Marwan Effendy (Media Mesin: Majalah Teknik Mesin, 2005)
The applications of sheet metal forming is very important in the automotiveindustries since most of the car components are produced by press formingprocesses. Survey shows that the role of numerical simulation and optimization toimprove performance and quality of their products are still very limited. Thispaper describes the use of MARC finite element code in a single stage sheet metalforming simulation on square cup deep drawing. The MARC’s results arevalidated with experimental results of benchmark problem square cup deepdrawing in Numisheet ’93. The paper also discusses the localized stress andstrain values of the formed part